Tunde Kelani: The Man Exceeds the Frame - Toyin Falola (Yoruba Studies Review)
The extraordinary announcement, coming from the Federal University of Agriculture, Abeokuta, that ace filmmaker Kelani will now be based there as a Fellow is heartwarming. The news reveals the warmth and uniqueness of the University’s boundless imaginations and the humanistic vision of its Vice-Chancellor, Professor Kolawole Salako. The news of this deserving appointment follows on the heels of Kelani receiving the prestigious Leopold ́ Sédar Senghor Prize for African Cultural Creativity and Impact in July, 2019 at the annual TOFAC event at Babcock University. In that same month, he was also inducted into the American Oscars—the Academy of Motion Picture, Arts and Sciences. All of these accolades are well-deserved. Kelani has spent his career putting things—people, ideas, cultures, traditions, and ideologies—inside the cinematographic frame. It is a most exciting thing to see him too bursting out of every frame with all these multiple achievements that celebrate him Ìrókò!